P160 A comparison of measurements of health-related quality of life in patients with sarcoidosis. (December 2018) - Atkins, CP; Jones, AP; Wilson, AM
Abstract : Introduction: Health-related quality of life (HRQoL) is an important consideration in patients with sarcoidosis as loss of QoL may be the primary driver for treatment. It is unknown how two commonly-used HRQoL questionnaires (EQ5D and SF-6D) compare. This study compared these two instruments and investigated their relationship to other clinical measures in patients with sarcoidosis. Methods: Participants with sarcoidosis completed five questionnaires; Kings Sarcoidosis Questionnaire (KSQ), Fatigue Assessment Scale (FAS), Hospital Anxiety and Depression Score (HADS), EQ5D and SF-6D. EQ5D and SF-6D health states were converted to health utility values using conversion spreadsheets based on UK population data. Correlation (Pearson's rho) between clinical parameters and utility values was performed to determine strength of association between factors. Linear regression modelling was performed to identify significant predictor clinical variables. Results: Ninety respondents returned questionnaires. Comparison of EQ5D and SF-6D utility values showed poor agreement, with the difference in utility values derived from the two scores seen to vary across the range of values seen (figure 1). SF-6D utility values showed strong correlation with FAS scores (r=−0.824) and KSQ general health status (r=0.866); EQ5D showed similar though slightly weaker correlation with these measures (r=−0.787 and 0.808 respectively). In the linear regression model FAS and HADS-Anxiety scores were significant predictors for SF-6D utility values but not EQ5D; KSQ general health status was a significant predictor for both EQ5D and SF-6D derived utility values. The models showed good fit for the SF-6D score (adjusted R 2 =0.802) but not EQ5D (adjusted R 2 =0.495). Conclusions: EQ5D and SF-6D showed significant differences in derived health states and utility values across this cohort. SF-6D appeared responsive to levels of anxiety and fatigue as well as disease-related health status. SF-6D appears to be a useful generic HRQoL questionnaire in patients with sarcoidosis and may better reflect the clinical problems affecting these patients.